Cultural Influences in Women-Friendly Labor- Saving Hand Tool Designs : - Kisaalita, William S.; Katimbo, Abia; Sempiira, Edison J.; Mugisa, Dana J. (Human Factors, 2016)
One of the reasons behind the gender asset gap among Sub-Saharan African women is the higher labor burden these women face, making it difficult for them to produce for the home and markets. Hand tools are the simplest form and therefore the best first step to address this problem. But designing women-friendly (sustainable) hand tools calls for better understanding of the low-resource settings where these women reside.
The Milk Churner Case